E Reduced left atrial rotational flow is independently associated with the risk of embolic brain infarcts. (6th June 2022) - Spartera, Marco; Stracquadanio, Antonio; Pessoa-Amorim, Guilherme; Harston, George; Mazzucco, Sara; Young, Victoria; Ende, Adam Von; Hess, Aaron T; Ferreira, Vanessa M; Kennedy, James; Neubauer, Stefan; Casadei, Barbara; et al.
Abstract : Introduction: Atrial fibrillation (AF) is a major risk factor for ischaemic stroke. Low blood flow velocities within the fibrillating left atrium (LA) are thought to predispose to activation of the coagulation cascade (1) and local thrombus formation (2), with consequent higher risk of cardioembolic stroke (1, 3-5). Nevertheless, up to 20-25% of embolic strokes occur in the absence of AF or any other identifiable cause (6, 7). 4D Flow cardiac magnetic resonance (CMR) studies have also shown that normal LA blood flow is typically vortical (8, 9) and such feature, in addition to high flow velocity, may play an important role in preventing thrombus formation by shear-mediated inhibition of platelet adhesion (10, 11). Despite this body of evidence, it remains unclear whether altered LA 4D flow characteristics are independently associated with cardioembolic stroke. Here, we evaluated the relationship between LA flow velocity and vorticity and large non-cortical or cortical brain infarcts (LNCCIs) which are likely to be embolic in origin (3, 12, 13), in patients with or without AF and either a previous history of ischaemic stroke or an increased clinical risk of stroke (i.e. CHA2 DS2 VASc score ≥1). Methods: Study Design: A total of 134 patients with either a previous history of ischaemic stroke or no history of stroke but a CHA2 DS2 VASc score ≥1 were recruited into the study and underwent a heart and brain magnetic resonance imaging (MRI) cross sectionally. MRI protocol: CMR scans were performed at 3T. For assessment of LA flow characteristics, all patients underwent ECG-gated time-resolved 3D phase-contrast CMR with 3-directional velocity encoding imaging ('4D-Flow') as previously described (14) using our post-processing tool (available at https://doi.org/10.5287/bodleian:ey4ovzdbB). Briefly, data analysis included 3D segmentation of LA volume, and determination of LA velocities and LA vorticity (Figure 1). Brain MRI protocol included analysis of detection of brain infarcts, defined as either large non-cortical infarcts and/or cortical infarcts(13), i.e. LNCCI. Results: A total of 134 individuals were included in the final analysis. Of these, a total of 67 (50%) had a diagnosis of AF and 58 (43%) were in AF at the time of the scan. Among the 67 (50%) participants in SR without a past history of AF, a new diagnosis of asymptomatic AF in 1 patient. Brain and cardiac magnetic resonance imaging On brain MRI, 39 participants (29%) displayed at least one embolic brain infarct (i.e. LNCCI), 20 (15%) had at least one small non-cortical infarct (i.e. non-embolic) without LNCCI, and 75 (56%) had no brain infarct. Baseline characteristics are reported in Table 1. Predictors of embolic brain infarcts After adjusting for rhythm at the time of the scan, each SD reduction in LA vorticity was associated with an approximately 2-fold higher risk of prevalent LNCCI [OR (95% CI) = 2.19 (1.20-4.01) per SD, P = 0.011]. Conversely, no significant association with LNCCIs was found for LA peak flow velocity (P = 0.40), or any of the other LA/LV functional/structural parameters investigated (all P>0.05). After further adjusting for age, history/evidence of AF, and CHA2 DS2 VASc score (Figure 2), LA vorticity remained significantly associated with LNCCIs [OR (95% CI) = 2.10 (1.12-3.92) per SD, P=0.021]. The observed age-, CHA2 DS2 VASc-, and rhythm-adjusted association between LA vorticity and LNCCIs remained significant after further adjusting for multiple covariate specifications (Figure 2, all P<0.05). In keeping with these results, LNCCIs were significantly more prevalent in those patients displaying the lowest level of LA vorticity than in the middle and highest levels of LA vorticity (P = 0.001; Figure 3). Discussion: The main finding of this cardiovascular and brain MRI study is that reduced LA blood flow vorticity is significantly and specifically associated with large, likely-embolic, brain infarcts (i.e., LNCCI) (15), independently of AF, age, clinical stroke risk, and LA and LV volumes and function. LNCCI are typically associated with worse neurological symptoms (15), cognitive decline (3), and a cardiac or vascular embolic source (7) compared with smaller non-cortical lesions, which are more likely to be of vascular origin. The fact that up to 20-25% of LNCCI remain of undetermined cause after a conventional full diagnostic evaluation suggests that some pathophysiologic mechanisms of embolic stroke are currently poorly characterized (6, 7). Our finding of an independent association between lower LA flow vorticity (by 4D Flow CMR) and LNCCI, but not with smaller non-cortical or lacunar infarcts, suggests that low LA flow vorticity may constitute a previously unrecognised risk factor for cardioembolic stroke, which may be used to identify patients that would benefit from tailored anti-thrombotic treatment for embolic stroke prevention. These could include both low-risk patients with AF (i.e., CHA2 DS2 -VASc 0-1) and patients in SR without any prior history of AF. In conclusion, reduced rotational LA blood flow is associated with embolic (but not lacunar) brain infarcts, independently of age, cardiac rhythm, stroke risk factors, and cardiac structure or function. Our study provides a clear rationale for investigating whether LA vorticity can identify individuals in SR or low-risk individuals with AF who would benefit from oral anticoagulation therapy for the prevention of cardioembolic stroke.